HUBUNGAN ANTARA STATUS GIZI STUNTING DAN PERKEMBANGAN BALITA USIA 12-59 BULAN - Ningrum, Ema Wahyu; Utami, Tin (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Stunting is a problem of chronic malnutrition caused by the lack of nutrient intake in a long time due to feeding that is not in accordance with nutritional needs. Toddlers who have stunting have a risk of decreased intellectual ability, productivity, and increased risk of degenerative diseases in the future. Descriptive analytic research design with cross sectional approach. The sample size of 60 toddlers aged 12-59 months consisted of 60 infants. Sampling technique purposive sampling. The data collected are categorical data. The instrument measures stunting using microtoase and z-score, to detect developments using Denver II. Univariate analysis with frequency distribution, bivariate analysis using chi square and alternative test Fisher Exact test. The result of this research is there is no correlation between nutritional status with infant development (p = 1,000), there is no relation between sex with development of toddler (p = 0,643), no relation between age with infant development (p = 0,307) between birth weight history and infant development (p = 0,612). Midwives pay more attention to the growth and development of stunting children and conduct continuous health education to the family about the impact and how to prevent stunting complications, to the family to give more attention to the child stunting and can provide optimal health efforts so that children can achieve the process of growth that is his age. Keywords: stunting nutrition status, development, toddlers